2017
DOI: 10.1007/s41669-017-0045-0
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Small Cell Lung Cancer: A Systematic Review of the Literature

Abstract: BackgroundSmall cell lung cancer (SCLC), the most aggressive form of lung carcinoma, represents approximately 15% of all lung cancers; however, the economic and healthcare burden of SCLC is not well-defined.ObjectiveThe aim of this study was to explore the impact of SCLC on healthcare costs through a systematic literature review (SLR).MethodsUsing the OVID search engine, the SLR was conducted in PubMed, MEDLINE In–Process, EMBASE, EconLIT and the National Health Service Economic Evaluation Database (NHS EED). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…As one of the most frequently diagnosed cancers, SCLC represents about 15% of lung neoplasms. 33 Compared with conventional chemotherapy, the surgical treatment of SCLC is much more effective. However, the high recurrence rate is still a difficult problem.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most frequently diagnosed cancers, SCLC represents about 15% of lung neoplasms. 33 Compared with conventional chemotherapy, the surgical treatment of SCLC is much more effective. However, the high recurrence rate is still a difficult problem.…”
Section: Resultsmentioning
confidence: 99%
“…Forth, social costs, such as out-of-pocket money and loss of productivities, were not included. In many other studies on the costs of lung cancer treatment, the out-of-pocket expenses were not considered due to their high uncertainty [ 27 ]. As of 2015, the coverage of health insurance by Korean government for cancer patients was 76% [ 28 ]; therefore, the total medical expenses actually paid by patients would be 1.3 times higher than reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…13 14 There has been an increase in the numbers of studies documenting the cost of various NCDs, however, the overwhelming majority of these studies have been conducted in developed countries or in low-income and middleincome countries in Asia. [15][16][17][18][19][20][21] Data from existing studies confirm the immense economic burden from NCDs. Muka et al in their review of the global impact of NCDs on healthcare found that globally, cancer and CVDs had the highest reported mean annual total direct costs per patient of approximately US$197 772 and US$81 096, respectively.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%